A study of prevalence of thyroid dysfunction in abnormal uterine bleeding - Rai, Aditi; Raina, Sapna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Abnormal uterine bleeding (AUB) is one of the most frequent presentation to gynecology OPD. AUB is a common but complicated clinical presentation and occurs in 15-20% of women between menarche to menopause and significantly affects the women’s health. Thyroid disorders are more common in women than in men and cause abnormal sexual development, menstrual irregularity, infertility and premature menopause. Objective of this study was to estimate the prevalence of thyroid disorders in women in reproductive age group with AUB. Methods: A hospital based prospective cross sectional observational study was carried out in department of obstetrics and gynecology, Mazumdar-Shaw Cancer and Medical Center and Narayana Hrudayalaya Hospital at Narayana Health City, Bangalore with abnormal uterine bleeding during the period of 2 years (December 2015 to November 2017), total 153 patients were included in the study. All women with AUB in reproductive age group were included. Diagnosed cases of ovarian cyst, uterine fibroid, polyp, adenomyosis, endometriosis and malignant (endometrial and cervical) tumors were excluded. Women who are on drugs or hormone therapy (for past 3 months. IUCD users/oral contraceptives pill user. Patients with known case of thyroid disorder, carcinoma thyroid patients with history of coagulation disorder, liver disorder, renal disorder, tuberculosis. Results: A total N=115 (75.2%) of patients who took part in this study had euthyroid status. The estimated prevalence of thyroid dysfunction was 24.9%. Out of which n=22 (14.4%) had subclinical hypothyroidism, n=14 (9.2%) had overt hypothyroidism, n=2 (1.3%) had hyperthyroidism. The most common thyroid dysfunction amongst the study group was noted to be subclinical hypothyroidism (14.4%). Conclusions: There is a high prevalence of thyroid disorders in cases which are clinically diagnosed as AUB. TSH is most sensitive test in detecting thyroid dysfunction. Subclinical cases need to be treated. Hence thyroid function evaluation should be made mandatory in cases of AUB to detect thyroid dysfunction.